Note to Mr. F. Jeffreys, Cork, signed "Square Deal" (1926)
Reads "Please hand attached to Mr Mason."
With cover addressed "Mr. F. Jeffreys, 55 Grand Parade, Cork", franked in Cork, 5 February 1926.
Keywords: Ireland -- History -- 1922-